Magnetic Resonance Spectroscopy of Adult Thalamic Glioblastoma Multiforme - Li, MD, MSc, Ping; Liu, MD, PhD, Yingru; Rowswell-Turner, PhD, Rachael; Esfahani, MD, Fraydoon (North American Journal of Medicine and Science, 2012)
Thalamic glioblastoma multiforme (GBM) is a rare malignant primary central nervous system (CNS) tumor. Here we report a case of adult unilateral GBM involving the right thalamus. The diagnosis of GBM was first indicated by a region of irregular enhancement with central necrosis in the thalamus, visualized with traditional magnetic resonance imaging (MRI) with contrast. Magnetic resonance spectroscopy (MRS), showing elevated lipid and lactate peaks, provided further evidence of GBM while rendering primary CNS lymphoma (PCNSL), anaplastic glioma, or metastasis less likely. The final diagnosis of GBM was confirmed by pathological examination of the tumor specimen. This report highlights the utility of combining MRS with other imaging modalities to facilitate the diagnosis of CNS lesions.